Resolvin D5 Inhibits Neuropathic and Inflammatory Pain in Male But Not Female Mice: Distinct Actions of D-Series Resolvins in Chemotherapy-Induced Peripheral Neuropathy - Luo, Xin; Gu, Yun; Tao, Xueshu; Serhan, Charles Nicholas; Ji, Ru-Rong (Frontiers in Pharmacology, 2019)
Earlier studies have demonstrated that essential fatty acid-derived specialized pro-resolving mediators (SPMs) promote the resolution of inflammation and pain. However, the potential analgesic actions of SPMs in chemotherapy-induced peripheral neuropathy (CIPN) are not known. Recent results also showed sex dimorphism in immune cell signaling in neuropathic pain. Here, we evaluated the analgesic actions of D-series resolvins (RvD1, RvD2, RvD3, RvD4 and RvD5) on CIPN in male and female mice. Paclitaxel (PTX, 2 mg/kg), given on day 0, 2, 4, and 6, produced robust mechanical allodynia in both sexes at 2 weeks. Intrathecal injection of RvD1 and RvD2 (100 ng, i.t.) reduced PTX-induced mechanical allodynia in both sexes, whereas RvD3 and RvD4 (100 ng, i.t.) had no apparent effects on both sexes. Interestingly, RvD5 (100 ng, i.t.) only reduced mechanical allodynia in male mice but not in female mice. Notably, PTX-induced mechanical allodynia was fully developed in Trpv1 or Trpa1 knockout mice, showing no sex-differences. Also, intrathecal RvD5 reduced mechanical allodynia in male mice lacking Trpv1 or Trpa1, whereas female mice with Trpv1 or Trpa1 deficiency had no response to RvD5. Finally, RvD5-induced male-specific analgesia was also confirmed in an inflammatory pain condition. Formalin-induced 2nd phase pain (licking and flinching) was reduced by intrathecal RvD5 in male but not female mice. These findings identified RvD5 as the first SPM that shows sex dimorphism in pain regulation. Moreover, these results suggest that specific resolvins may be used to treat CIPN, a rising health concern in cancer survivors.